2004
DOI: 10.1097/01.inf.0000115502.94265.df
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulsed field gel electrophoresis patterns of Bordetella pertussis isolates from unvaccinated children with severe or mild pertussis

Abstract: Differences in virulence of circulating B. pertussis strains can be absent or might not correlate with specific PFGE patterns. Other methods should be evaluated to identify differences in virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Bisgard et al (29) found no association between PFGE profiles of isolates (n=226) collected during 1989–1996 and hospitalisation, or pneumonia among infants. Neither did Heininger et al (30) notice differences in PFGE patterns between unvaccinated children with severe symptoms (n=31) compared with isolates from matched children with mild symptoms (n=32). Their rather small material was collected during a 10–year period beginning in 1990.…”
Section: Discussionmentioning
confidence: 84%
“…Bisgard et al (29) found no association between PFGE profiles of isolates (n=226) collected during 1989–1996 and hospitalisation, or pneumonia among infants. Neither did Heininger et al (30) notice differences in PFGE patterns between unvaccinated children with severe symptoms (n=31) compared with isolates from matched children with mild symptoms (n=32). Their rather small material was collected during a 10–year period beginning in 1990.…”
Section: Discussionmentioning
confidence: 84%
“…PFGE patterns of B. pertussis isolates from children with severe disease were recently compared with those of strains isolated from children with mild disease. Interestingly, variability in the severity of pertussis was not attributed to a specific PFGE profile or 'supervirulent' clones [78]. This reduces concerns regarding selection of novel B. pertussis strains with increased virulence that may potentially cause epidemics.…”
Section: Germanymentioning
confidence: 98%